In vitro gene silencing effect of chitosan/shRNA PDGF-D nanoparticles in breast cancer - EKENTOK ATICI, CEYDA; ÖZBAŞ, SUNA (MARMARA UNIV, FAC PHARMACY, 2017)
Breast cancer is the most common cancer worldwide in women and it is highly malignant and fatal. PDGF-D plays role in regulation of many cellular processes such as angiogenesis. PDGF-D is overexpressed in many types of cancers and promote tumor growth and metastasis. Silencing of PDGF-D gene by using shRNA with an appropriate carrier system may decrease tumor growth and metastasis. In our study, we prepared chitosan nanoparticles loaded with five different shRNA plasmids targeting different exons of PDGF-D gene. Then, nanoparticles were characterized in vitro and transfection efficiency of these nanoparticles were investigated in breast cancer cell lines (MCF7, MDA-MB-231 and MDA-MB-435). The effects of single and multiple shRNA sequences, molecular weight of chitosan (150 kDa and 400 kDa) and the amount of shRNA (100 and 500 mu g) on the characterization and transfection efficiencies of nanoparticles have been studied. Size of nanoparticles changed between 200-400 nm and approximately 95-100% encapsulation efficiency were obtained. Release of shRNA changed with the molecular weight of chitosan. It was obtained that formulation containing shRNA plasmid targeting PDGF-D exon 6 (NP1) has the highest silencing efficiency in MDA-MB-231 cell line. It was also evaluated that chitosan can be a suitable gene delivery system for shRNA targeting PDGF-D.
Keywords: Breast cancer; chitosan; shRNA; gene silencing; RNAi; GROWTH-FACTOR-D; EPITHELIAL-MESENCHYMAL TRANSITION; TRANSFECTION EFFICIENCY; RNA INTERFERENCE; RECEPTOR; CELLS; DNA; PROGRESSION; CARCINOMA; THERAPY